Enhancing court capacity to enforce education rights: judicial tools used in Abbott v. Burke - Sciarra, D (Foundation for Law, Justice and Society, 2009)
This policy brief examines a critical aspect of quality education litigation: the tools available to courts to fashion and ensure implementation of a constitutional method of funding public education to improve schools. As a case study, the brief analyzes the techniques employed by the New Jersey Supreme Court in providing a remedy to disadvantaged urban school children in the long-running Abbott v. Burke case. The Abbott litigation offers important lessons on how courts can improve their competency to fashion and direct implementation of a remedy to vindicate constitutionally guaranteed socio-economic rights, particularly when they implicate politically vulnerable or disenfranchised groups or classes of citizens.